2010
DOI: 10.1089/fpd.2009.0373
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Treatment of Animal Feed and Water for the Control ofSalmonella

Abstract: The control of Salmonella in animal feedstuffs is important, principally to protect the human food chain from contamination by Salmonella derived from infected animals. The transmission of Salmonella from animal feeds to animals, and onward to human food products, has been convincingly documented. This is especially important for chicken breeding and laying flocks and pigs, in view of the consequences of recent or imminent control legislation in the European Union. Animal feed ingredients, particularly animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 111 publications
0
74
0
7
Order By: Relevance
“…Salmonella may also be found in compounded feed and even in heat-treated and pelleted feed due to environmental contamination of feed mills and the high likelihood for cross contamination in the feed mill and during transport and storage at the farm (Binter et al, 2011;Jones, 2011). The difficulties in sampling and culturing Salmonella from feed sources may lead to an underestimation of this risk (Davies and Wales, 2010). Many studies indicate and have shown that contaminated feed is a risk for the introduction of Salmonella onto the farm (Davies et al, 2004;Molla et al, 2010).…”
Section: Control Of Salmonella In Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella may also be found in compounded feed and even in heat-treated and pelleted feed due to environmental contamination of feed mills and the high likelihood for cross contamination in the feed mill and during transport and storage at the farm (Binter et al, 2011;Jones, 2011). The difficulties in sampling and culturing Salmonella from feed sources may lead to an underestimation of this risk (Davies and Wales, 2010). Many studies indicate and have shown that contaminated feed is a risk for the introduction of Salmonella onto the farm (Davies et al, 2004;Molla et al, 2010).…”
Section: Control Of Salmonella In Feedmentioning
confidence: 99%
“…The best efficacy results and lowest masking were achieved for a formaldehyde-containing product (Carrique-Mas et al, 2007). A thorough review of the use of various chemicals to reduce Salmonella contamination of feed contamination has recently been published (Wales et al, 2010).…”
Section: Control Of Salmonella In Feedmentioning
confidence: 99%
“…Interventions such as vaccination (Tenk et al, 2000;Thain et al, 1984), antibiotic treatment (Reynolds et al, 1997), acidification of feed or water (Wales et al, 2010a) or adding inhibitory substances such as lime to litter (Bennett et al, 2005) may also reduce the level of Salmonella in faeces or the sampled environment, making detection more difficult. In the antimicrobial hatchery treatment of breeding flocks or use of formaldehyde during hatching may also inhibit detection (Cadirci, 2009).…”
Section: Factors Influencing the Detection Of Salmonella In Breeding mentioning
confidence: 99%
“…The primary method used to reduce animal feed contamination is to monitor and control bacterial contamination of ingredients and equipment used in the manufacturing and processing of the raw material (Wales et al, 2010). However, microbiological control can also be achieved with the addition of chemical products to the feed (Dibner and Buttin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, microbiological control can also be achieved with the addition of chemical products to the feed (Dibner and Buttin, 2002). Some chemicals that can control bacterial proliferation are organic acids (acetic acid, propionic acid, and salts of citric and formic acid), ethanol, formaldehyde, alcohol, zinc propionate, and zinc acetate, but the efficiency of these compounds can vary (Wales et al, 2010).…”
Section: Introductionmentioning
confidence: 99%